The effects of soybean hulls in corn-soybean meal and corn-soybean meal-dried distillers grains with solubles diets on nursery pig performance - Goehring, D.L.; James, B.W.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Two experiments were conducted to evaluate the effects of soybean hulls in diets with and without corn dried distillers grains with solubles (DDGS) on nursery pig growth performance. In Exp. 1, a total of 600 pigs (PIC C-29 × 359, initially 14.7 lb) were used in a 42-d growth study. Diets contained increasing amounts of soybean hulls (0, 3, 6, 9, or 12%) in either corn-soybean meal or corn-soybean meal-DDGS–based diets (15 and 30% DDGS for Phases 1 and 2, respectively). Pigs were blocked by initial pen weight, gender, and room location, with 10 pigs per pen and 6 replications per treatment. Overall (d 0 to 42), soybean hulls × DDGS interactions (quadratic, P < 0.05) were observed for F/G and caloric efficiency on an ME and NE basis. Increasing soybean hulls worsened F/G quadratically (P < 0.03) when added to diets without DDGS but linearly (P < 0.01) when added to diets with DDGS. Caloric efficiencies improved on an ME and NE basis (quadratic, P < 0.04) with increasing soybean hulls in diets without DDGS but did not influence caloric efficiency when added to diets containing DDGS. Adding DDGS to the diet decreased (P < 0.04) ADG and ADFI but tended to improve (P < 0.06) F/G. Adding soybean hulls to diets containing DDGS further reduced (quadratic, P < 0.05) ADG and tended to reduce (quadratic, P < 0.08) ADFI, whereas adding soybean hulls to diets without DDGS had no effect on ADG or ADFI.
Keywords: Swine; DDGS; Growth; Nursery pig; Soybean hulls